Pengaruh Kebijakan Subsidi Pupuk terhadap Produksi Gula Kristal Putih Indonesia - Aditya Arief Rachmadhan; Nunung Kusnadi; Andriyono Kilat Adhi (Jurnal Agro Industri Perkebunan, 2020)
The direction of government policy is to increase plantation white sugar production. The government through the Ministry of Agriculture has launched fertilizer subsidies to support increased plantation white sugar production. Nevertheless, Indonesia's plantation white sugar production tends to experience a decline from year to year. This condition is not in line with the objectives. This study aims to evaluate the fertilizer subsidy policy in order to achieve the national plantation white sugar self-sufficiency target. The study uses multiple linear regression methods with time series data. The results of the analysis show that the application of the subsidized fertilizer policy does not significantly affect the production of plantation white sugar from sugar cane farmers. The area of sugarcane plantation is a factor that significantly influences the production of Indonesian plantation white sugar.